Percepção da qualidade de vida em idosas praticantes de hidroginástica - Zucolo, Andre Chang Menassi [UNIFESP] (2018)
Introduction: The Number Of Elderly People In Brazil And In The World Has Increased Enormously. Dought Of This Reality, National And International Mobilizations Must Be Initiated And Localized For Political And National Purposes. Thus, The Challenge Arises Of Promoting A Healthy Process, Of Improving Or Maintaining A Good Quality Of Life. The Practice Of Physical Exercise And, Mainly, Water Aerobics, Has Been Advocated As An Important Resource For The Achievement, But It Is Still Scarce As An Investigation About The Habits Of Physical Exercise. Objective: The Objective Of This Research Was To Verify If There Is Participation Of A Hydrogymnastics Program In The Thematic Classes As A Sample Of The Quality Of Life, Recognizing The Practice Of Hydrogymnastics As A Relevant Element To This One. The Practice Is An Advanced Water Practice In The Perception Of The Quality Of Life Of The Elderly. Materials And Methods: The Research Is Descriptive And Exploratory, Having A Qualitative-Quantitative Approach. It Involved